Contrast-enhanced MR microscopy of amyloid plaques in five mouse models of amyloidosis and in human Alzheimer’s disease brains - Clémence Dudeffant (Nature Portfolio, 2017)
Abstract Gadolinium (Gd)-stained MRI is based on Gd contrast agent (CA) administration into the brain parenchyma. The strong signal increase induced by Gd CA can be converted into resolution enhancement to record microscopic MR images. Moreover, inhomogeneous distribution of the Gd CA in the brain improves the contrast between different tissues and provides new contrasts in MR images. Gd-stained MRI detects amyloid plaques, one of the microscopic lesions of Alzheimer’s disease (AD), in APPSL/PS1M146L mice or in primates. Numerous transgenic mice with various plaque typologies have been developed to mimic cerebral amyloidosis and comparison of plaque detection between animal models and humans with new imaging methods is a recurrent concern. Here, we investigated detection of amyloid plaques by Gd-stained MRI in five mouse models of amyloidosis (APPSL/PS1M146L, APP/PS1dE9, APP23, APPSwDI, and 3xTg) presenting with compact, diffuse and intracellular plaques as well as in post mortem human-AD brains. The brains were then evaluated by histology to investigate the impact of size, compactness, and iron load of amyloid plaques on their detection by MRI. We show that Gd-stained MRI allows detection of compact amyloid plaques as small as 25 µm, independently of their iron load, in mice as well as in human-AD brains.